(untitled) (Research, Society and Development, 2024)
Bell’s palsy is a non-progressive neurological disorder of the facial nerve, being a highly debilitating condition, both in aesthetic and functional terms, and treatment with botulinum toxin injections, with or without neuromuscular therapy, together with fillers, has shown promising results in restoring normal facial features. Given the possibilities of using botulinum toxin and additional treatment with hyaluronic acid in facial and functional aesthetics, the objective is to present a clinical case of this application for the correction of facial asymmetry caused by Bell’s palsy. This is a report of a 37-year-old female patient with hemifacial paralysis. Hyaluronic acid and botulinum toxin fillers were used. The results demonstrated a marked improvement in facial symmetry and, according to the patient, the treatment restored her self-esteem and, consequently, her quality of life. It is concluded that the use of botulinum toxin type A and hyaluronic acid are very safe and effective, as long as they are carried out under the guidance of a professional trained in their therapeutic and cosmetic use and the asymmetries caused by Bell’s palsy can be treated in a effectively by these methods. In this report, it was possible to observe a significant improvement in the symmetry, balance and muscular function of the patient’s face, as well as in psychosocial aspects, contributing to a better quality of life and increased self-esteem.